Consumer-based brand equity : relationship between country of origin and brand equity dimension - Syed Shah Alam,; Zizah Che Senik,; Nor Asiah Omar,; Mohd Helmi Ali, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Consumer-based brand equity is essential in marketing strategy as it can affect firm performance. This study examines the relationship between country of origin effect on consumer-brand equity, for a selected product category in Malaysian market. In this context, a conceptual research model was developed based on previous literature of brand equity. Convenient sampling procedure was used in this research using self-administered questionnaire to collect data from a total of 378 car buyers in Klang Valley, Malaysia. This study tested eight hypotheses. The multiple regression result shows that country of origin is one of the important predictors for brand awareness, brand association, perceived quality and brand loyalty. Both implication of research and implication of practice are discussed.